Training of Paralegal Communication Technique at PDNA Ngawi - Marisa Kunianingsih; Muchamad Iksan; Syaifuddin Zuhdi; Gilang Rahmat Allam (Jurnal Pengabdian Masyarakat Bestari, 2023)
Communication is the most important thing in everyday life. Paralegals need skills in communication to optimize the services they provide. So, this activity aims to equip paralegals with good and correct communication techniques, which are a basic requirement, so that they can optimize their abilities. The method applied in this training activity was socialization, which was organized by the UMS Master of Law program in collaboration with PDNA Ngawi. Each paralegal in this training receives an explanation of the theory and practices communication techniques. This training has a positive impact on paralegals, who will be in charge of carrying out their main duties and functions in providing legal aid services to the wider community.